Postcholecystectomy syndrome: the modern approach: resolution of Advisory council - V. T. Ivashkin; A. V. Okhlobystin; D. S. Bordin; E. Ya. Seleznyova; Yu. A. Kucheryavy; Ye. V. Bystrovskaya; O. C. Vasnev; M. F. Osipenko; G. H. Musayev; Yu. O. Shulpekova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of publication. To present proceedings of Advisory council on postcholecystectomy syndrome (August 25, 2017; Prague, Czech Republic) with support of the Adamed Group company. Summary. The Advisory council proposed algorithm for investigation and management of patients with postcholecystectomy syndrome (PCS). Gallstone disease (GSD) is diagnosed in 10-25% of the population of various age, with obvious trend to involvement of the younger patient categories in the last decades. The total number of GSD patients increases every decade no less than twice. Cholecystectomy remains the basic method of surgical treatment of symptomatic GSD. Nowadays laparoscopic cholecystectomy became universally popular and earned the status of the «gold standard» of surgical treatment. At the same time at asymptomatic GSD the watchful waiting approach avoiding active treatment is considered to be the most expedient. Biliary sludge and microlithiasis including cases undiagnosed at routine investigation can be one of important factors for development of the PCS. Pharmacological treatment of sphincter of Oddi dysfunction that develop at GSD/PCS include following of dietary recommendations, intake of selective spasmolytics, digestive enzymes and ursodeoxycholic acid. Conclusions. Follow-up program for the patient of the cholecystectomy should include regular assessment of clinical symptoms for duly diagnostics of acute and/or severe complications and associated diseases, that may require surgical treatment. Treatment has to include regular courses of selective antispasmodics, the presence of indications - prescription of bile acid supplements, when required - methods of endoscopic surgery.